ANALISIS FAKTOR PENDUKUNG INVESTASI UNTUK PENINGKATAN GAIRAH INVESTASI DI KOTA SEMARANG - - Hardiwinoto; Andwiani Sinarasri; Akhmad Fathurrohman (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The research aims to identify of invesment supporting in the city of Semarang. Variabbes of this research are institutional role, zoning of city, and infrastructure. The method used to survey onidentification and respons from entrepreneurs about potential investment supporting in the city ofSemarang. The analytical methods to identified of potential investment supporting and usedmultiple regresion. The results of the study are known that in investment supporting of SemarangCity are institutional role, zoning of city, and insfrastructure. But zoning of city is not influencesignificance. Results of significance are institutional role 0.049, zoning of city 0.188 andinfrastructure 0.018 base on the results account known that most influence is infrastructures. Theresults of the study are useful to provide recommendations to the government about system andprocedures to investments and improve several infrastructure of city to support invesment, thusincreasing the competitiveness of the city of Semarang.Keywords: institutional role, zoning of city, and insfrastructure.